Pengaruh Permainan Ular Tangga Terhadap Kemampuan Motorik Kasar Anak - Dewi Yulan; Durrotunnisa, Durrotunnisa; Sita Awalunnisa; Sofiyanti Nur Zuama (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Gross motor development is a fundamental aspect of early childhood because it requires coordination of large muscles that support movement and daily activities. Unfortunately, many children do not receive adequate stimulation to strengthen these abilities. One alternative is through traditional games such as snakes and ladders, which are enjoyable and at the same time enhance balance, coordination, and muscle strength. This study aimed to examine the effect of snakes and ladders on the gross motor skills of Group A children at TK Negeri Lantula Jaya, Morowali Regency. The research used a quantitative approach with a quasi-experimental one-group pretest–posttest design involving 12 children. Data were collected through observation, documentation, and interviews using assessment sheets focused on balance, coordination, and strength. The findings indicated a significant improvement in gross motor skills after the intervention, with more children reaching the “Developing as Expected” and “Very Well Developed” categories. A paired sample t-test resulted in a significance value of 0.000 < 0.05, confirming that snakes and ladders is an effective and engaging medium to stimulate gross motor development in early childhood.